Effects of enrichment strategies on outcome of adrecizumab treatment in septic shock: Post-hoc analyses of the phase II adrenomedullin and outcome in septic shock 2 trial - van Lier, Dirk; Picod, Adrien; Marx, Gernot; Laterre, Pierre-François; Hartmann, Oliver; Knothe, Claudia; Azibani, Feriel; Struck, Joachim; Santos, Karine; Zimmerman, Jens; Bergmann, Andreas; Mebazaa, Alexandre; et al. (Frontiers in Medicine, 2022)
Purpose Adrecizumab, a non-neutralizing antibody of adrenomedullin (ADM) was recently investigated regarding its potential to restore endothelial barrier function in septic shock patients with high plasma ADM levels. Circulating dipeptidyl peptidase 3 (cDPP3), a protease involved in the degradation of several cardiovascular mediators, represents another biological pathway strongly associated with outcome in septic shock, although unrelated to ADM. Therefore, the prognosis of patients with elevated cDPP3 may not be influenced by Adrecizumab. Also, time until initiation of treatment may influence efficacy. Objective To evaluate effects of cDPP3-based enrichment on treatment efficacy of Adrecizumab. Materials and Methods Post-hoc analysis of AdrenOSS-2, a phase-II, double-blind, randomized, placebo-controlled biomarker-guided trial of Adrecizumab. Results Compared to the total study cohort [HR for 28-day mortality of 0.84 (95% CI 0.53;1.31), p = 0.439], therapeutic benefit of Adrecizumab tended to be more pronounced in the subgroup of 249 patients with low cDPP3 (<50 ng/mL); [HR of 0.61 (95% CI 0.34;1.08), p = 0.085]. Median duration to study drug infusion was 8.5 h. In the subgroup of 129 patients with cDPP3 <50 ng/mL and an early start of treatment (<8.5 h after septic shock diagnosis) HR for 28-day mortality vs. placebo was 0.49 (95% CI 0.21–1.18), p = 0.105. In multivariate interaction analyses corrected for baseline disease severity, both cDPP3, as well as the cDPP3 * treatment interaction term were associated with a reduced HR for 28-day mortality in the Adrecizumab treated group; p = 0.015 for cDPP3 in univariate analysis, p = 0.025 for the interaction term between cDPP3 and treatment group. In contrast, treatment timing was not significantly associated with 28-day mortality in multivariate interaction analyses. Discussion In septic shock patients with high ADM levels, a further post-hoc enrichment strategy based on cDPP3 may indicate (with all the caveats to be considered for post-hoc subgroup analyses) that therapeutic efficacy is most pronounced in patients with lower cDPP3 levels.